Accountability in EU security and defence : the law and practice of peacebuilding - Moser, Carolyn, 1986- (Oxford : Oxford University Press, 2020)
This book offers the first comprehensive legal analysis and empirical study of accountability concerning the EU's peacebuilding endeavours-also referred to as civilian crisis management. Since 2003, the EU has launched more than twenty civilian missions under the CSDP in conflict-torn regions in Eastern Europe, the Western Balkan, sub-Saharan Africa, the Middle East, and South East Asia with the aim of restoring stability and security. Mission mandates cover a broad range of multidimensional tasks, such as border monitoring, rule of law support, police training, law enforcement capacity building, and security sector reform. In light of these numbers and tasks and given (recent) alarming insights from practice, it begs the question who is accountable (to whom) for the EU's manifold extraterritorial peacebuilding activities.
Also issued in print: 2020.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on June 2, 2020).
Keywords: European Security and Defense Policy; Peace-building -- International cooperation